Rancang Bangun Monitoring Early Warning System Bencana Banjir Berdasarkan Ketinggian Aliran Sungai Mengunakan Modem SIM900 dan Internet of Things - Sumardiono, Arif; Alimudin, Erna; Zaenurrohman; Susanti, Hera (Infotekmesin, 2022)
The rainfall in the Cilacap region is high, about 80-100mm in October-March. The high rainfall that causes the overflow of river water is unpredictable. The high water discharge is not realized until the river water overflows and causes flooding. Therefore, a river water level monitoring system is needed to detect river overflows early. This tool uses a solar cell as a power supply. The monitoring system is divided into two points of river water level monitoring system with a distance between points for the laboratory scale stage, which is 100 meters. Sensors that measure the height of river flow are ultrasonic sensors. The sensor results are processed by microcontroller and SIM 900 L module to be sent to the database. When the water level is in the Alert level 3, the buzzer will sound as a warning. The ultrasonic sensor test results have a very small error. Sensor 1 has an average error of 0.00023% and ultrasonic sensor 2 has an error of 0.00016%. The system is able to transmit river water level data that can be accessed through the website.